KẾT QUẢ NGHIÊN CỨU HẬU QUẢ CHẤT DA CAM/DIOXIN ĐỐI VỚI SỨC KHỎE CON NGƯỜI CỦA TRUNG TÂM NHIỆT ĐỚI VIỆT - NGA GIAI ĐOẠN 1988 - 2022 - Trịnh, Khắc Sáu; Võ, Viết Cường (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH ISSUES ON THE CONSEQUENCES OF AGENT ORANGE/DIOXIN FOR HUMAN HEALTH OF THE JOINT VIETNAM - RUSSIA TROPICAL SCIENCE AND TECHNOLOGY RESEARCH CENTER BETWEEN 1988 AND 2022 During the period 1988 - 2022, the Joint Vietnam - Russia Tropical Science and Technology Research Center conducted the studies on the long-term biomedical consequences of Agent Orange/dioxin in Vietnam on many groups of subjects with different exposure levels including people residing and living in herbicide sprayed areas and areas around dioxin hotspots, veterans exposed to Agent Orange/dioxin during the war in the southern battlefield, and northern residents after the war migrated to areas sprayed with herbicides. The current status of effects of Agent Orange/dioxin on human health has been reviewed. The research results have provided scientific recommendations, opening the prospect for finding methods to protect people against dioxins and other persistent organic pollutants, effectively addressing the social problems associated with losses in health and quality of life. The long-term biomedical consequences of Agent Orange/dioxin for humans are still unpredictable, especially exposure at low doses and at trace concentrations. Therefore, it is necessary to further study the risks of ecotoxicants at low doses, and the changes in homeostasis and health of people residing and working in areas contaminated with Agent Orange/dioxin, including in secondary contaminated areas.